Is it time to bet on a fashion retailer? : Valuation of INDITEX S.A. - Nguyen, Phuong Anh (2019)
This thesis starts with the description of a company Inditex, its core operations and its business model. The work also maps the current trends in the fashion and apparel industry in order to conduct a strategic analysis and determine factors that might influence the company’s share value. Joined by a financial analysis as well as competitors’ analysis the work ends with a valuation part where the goal is to arrive at the company’s fair market value and provide an investment recommendation.